BRESSER-PEREIRA, Luiz Carlos. Macroeconomia da estagnação. Crítica da ortodoxia convencional no Brasil pós 1994. São Paulo: Editora 34, 2007, p. 325. - Santos, Santos Bruno (Geografia em Atos (Online), 2011)
Resenha.